Health utility and quality of life in pediatric liver transplant recipients. (26th April 2020) - Bharij, Aashiv; Neighbors, Katie; Alonso, Estella M.; Mohammad, Saeed
Abstract: To measure HU and HRQOL in pediatric liver transplant (LT) recipients, a cross‐sectional study of patient‐parent dyads was conducted. Direct HU were assessed in 48 adolescents ≥12 years using SG and TTO techniques. Indirect HU were measured by Health Utility Index 2 and HUI3 for subjects ≥12 years and CHU9D for ≥7 years. Patients reported HRQOL using PedsQL™ GC and PedsQL™ TM. A total of 108 dyads participated (55.6% female; 73.2% Caucasian; 42.6% biliary atresia; 35.2% living donor; 37.0% Medicaid). Mean age at survey was 13.6 ± 3.5 years, and time from LT was 8.9 ± 4.9 years. 61.2% were on monotherapy, 25 (23.2%) had acute rejection within 3 years, and 15 (13.9%) had a biliary obstruction within 5 years. Mean indirect HU and HRQOL scores by child report were lower than norms ( P  < .001). LRD recipients had higher PedsQL™ GC, PedsQL™ TM, and HUI3 scores ( P  < .01). HU in pediatric LT recipients are lower than norms. Availability of HU scores for post‐transplant health states will enable measurement of quality‐adjusted life years for future comparative effectiveness studies.